AUDIT FORENSIK TERHADAP PENGELOLAAN DAN PERTANGGUNGJAWABAN KEUANGAN NEGARA (STUDI KASUS PADA BADAN PEMERIKSA KEUANGAN RI) - Vita Lediastuti; Umar Subandijo (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2014)
This study aimed to compare the theory with the practice of forensic audit on field audit of the Goverment Financial Management and Its Reporting in joint audit activities of the financial year 2009 at The Ministry of National Education Inspectorate General conducted by the Auditor BPK RI. In addition, the study was conducted to analyze the internal control system as well as the identification of fraud that occurs in these activities. The results shows that the auditors of BPK RI have implemented some of the audit techniques that exist in forensic audit theory. The system of internal control and accountability in managing public finance influence on the size of the potential for fraud. The weakness of the internal control system led to a fraud committed in the management and accountability of state finances the joint audit activities of the Inspectorate General of the Ministry of National Education in financial year 2009, among others, the abuse of authority and accountability of the use of fictitious letters in accountability activities trips.